Predictors of Quality of Life Quality of Adults with Coronary Artery Disease (CAD) - Zuriati Zuriati; Farida Moh. Said; Milya Novera (UM Purwokerto Press, 2021)
Quality of Life is as a predictor of general wellbeing that is an important outcome in the treatment of any chronic disease. Impaired quality of life has increasingly become the most significant health outcome for CAD patients. The purpose of this study was to identify the predictor of quality of life of adults with CAD Patients. A descriptive cross-sectional study was conducted with sample of 125 participants of age between 35 to 64 years from RSUP. Dr. M. Djamil Hospital, Padang, West Sumatera, Indonesia. Each participant was administrated structured questionnaires, including the socio-demographic questionnaire, the CADE-Q questionnaire, Social Support questionnaire, general health perception, and the World Health Organization Quality of Life-BREF (WHOQOL-BREF). A regression model showed that Income, Duration of CAD, and general health perception were the predictors of patient’s quality of life (Adjusted R2 = .031, p < .01). Better understanding of the relationship between its predictor and quality of life is necessary to develop a suitable nursing intervention program to enhance patient’s quality of life.